2016
DOI: 10.1002/cpdd.244
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics, Safety, and Tolerability of Fevipiprant (QAW039), a Novel CRTh2 Receptor Antagonist: Results From 2 Randomized, Phase 1, Placebo‐Controlled Studies in Healthy Volunteers

Abstract: We evaluated the pharmacokinetics (PK), safety, and tolerability of a novel oral CRTh2 antagonist, fevipiprant (QAW039), in healthy subjects. Peak concentrations of fevipiprant in plasma were observed 1‒3 hours postdosing. Concentrations declined in a multiexponential manner, followed by an apparent terminal phase (t1/2, ∼20 hours). Steady state was achieved in 4 days with <2‐fold accumulation. Elimination was partly by renal excretion (≤30% of the dose) and glucuronidation. Food had minimal impact on the PK o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Two phase 1 studies investigated the pharmacokinetics (PK), safety, and tolerability of fevipiprant after single and multiple ascending doses in healthy subjects (Erpenbeck et al, 2016). On administration of single and multiple oral doses, fevipiprant peak plasma concentrations were observed 1-3 hours after the dose, and the apparent terminal half-life was approximately 20 hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two phase 1 studies investigated the pharmacokinetics (PK), safety, and tolerability of fevipiprant after single and multiple ascending doses in healthy subjects (Erpenbeck et al, 2016). On administration of single and multiple oral doses, fevipiprant peak plasma concentrations were observed 1-3 hours after the dose, and the apparent terminal half-life was approximately 20 hours.…”
Section: Introductionmentioning
confidence: 99%
“…An acyl-glucuronide (AG) metabolite without DP 2 antagonist activity was detected in plasma. Fevipiprant was well-tolerated at single and multiple oral doses up to 500 mg/day (Erpenbeck et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Before experimentation, ASM cells from each individual donor were incubated in media in the presence of a selective DP 2 agonist [DK-PGD 2 ; Cayman Chemical Company] (30) or selective DP 2 antagonists [CAY10471, OC000459, and fevipiprant, Cayman Chemical Company and Novartis (31)(32)(33) versus appropriate vehicle controls: dimethyl sulfoxide (DMSO) for DK-PGD 2 , CAY10471, and OC000459 and 10% dH 2 O in DMSO for fevipiprant].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Preliminary data confirm a good safety profile and improvement of FEV1, especially in patients with more severe obstruction. 68 Another Phase II study in patients with uncontrolled allergic asthma showed no improvement in pulmonary function. However, a subgroup analysis revealed that patients with impaired respiratory function (FEV1 <70%) had improved pulmonary function and asthma control when treated with QAW039.…”
Section: Antagonist Of the Prostaglandin D2 Receptormentioning
confidence: 99%